We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
468
1
avatar

8(4x+8)=11-(x+2)

 Mar 18, 2015

Best Answer 

 #1
avatar+142 
+5

simplify each side of the equation first.

 

8*4x + 8*8 = 11*-x + 11*-2

 

32x + 64 = -11x - 22

-64                     -64

 

32x = -11x - 86

+11x     +11x

 

43x = -86

/43       /43

 

x = -2

 Mar 18, 2015
 #1
avatar+142 
+5
Best Answer

simplify each side of the equation first.

 

8*4x + 8*8 = 11*-x + 11*-2

 

32x + 64 = -11x - 22

-64                     -64

 

32x = -11x - 86

+11x     +11x

 

43x = -86

/43       /43

 

x = -2

samgelinas Mar 18, 2015

5 Online Users

avatar